2014
DOI: 10.3390/molecules19068363
|View full text |Cite
|
Sign up to set email alerts
|

Properties for Sourcing Nigerian Larvicidal Plants

Abstract: Aedes aegypti is the primary vector of chikungunya, yellow and dengue fevers. Dengue fever is the major cause of child morbidity and hospitalisation in some Asian and African countries, while yellow fever is prevalent in Nigeria. The development of resistance to the available insecticides has necessitated the continued search for safer ones from plants. Eighteen plant extracts with ethnomedical claims of or demonstrated febrifuge, antimalarial, insecticidal and insect repellent biological activities were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Bhattacharya et al (2014b), Ndiok et al (2016) also reported that Culex quinquefasciatus transmits lymphatic filariasis. Adebajo et al (2014) reported that Aedes aegypti transmits chikungunya, yellow and dengue fevers. The occurrence of the vectors may be attributed to climatic conditions.…”
mentioning
confidence: 99%
“…Bhattacharya et al (2014b), Ndiok et al (2016) also reported that Culex quinquefasciatus transmits lymphatic filariasis. Adebajo et al (2014) reported that Aedes aegypti transmits chikungunya, yellow and dengue fevers. The occurrence of the vectors may be attributed to climatic conditions.…”
mentioning
confidence: 99%
“… Used to treat diabetes, ulcer, osteoporosis and anemia [155] Isolated probiotic strains did at 5000 mg/kg and 1000 mg/kg did not induce acute or subchronic toxicity in rats [156] Monkey pox Enantia chlorantha Oliv. Used to treat malaria, boils, yellow fever, hepatitis, jaundice, typhoid fever, tuberculosis in Africa [157] Induced antiviral and larvicidal effect against yellow fever virus and vector, anticonvulsion and antimicrobial activity [ 41 , 157 , 158 ] Ethanol stem bark extract induced toxicity at high dose [159] Poliomyelitis, meningitis, lassa fever, yellow fever Erythrina senegalensis DC. Used to treat malaria, fever, infections, pneumonia, neuralgic malaria, jaundice, pain, diarrhea and typhoid fever in Mali [160] .…”
Section: Discussionmentioning
confidence: 99%
“…Raven Used to treat nervous diseases, edema, dysentery, nephritis, diarrhea, headache and orchitis [209] Extract at 800 mg/kg did not induce toxic effect on BALB/c mice for 28 days [209] Meningitis Mangifera indica Leaf decoction is used to treat hepatitis in Burkina Faso and Uganda. Used to treat gastrointestinal, respiratory and genitourinary diseases, burn, itch, fever, cough, scurvy and throat/mouth infection [ 15 , 16 , 210 , 211 ] Mangiferin induced antiviral activity and controlled HSV replication, Larvicidal effect against yellow fever vector [ 41 , 211 ] Aqueous stem bark extract induced adverse effect and decreased the survival rate and emergence of younger flies of drosophila melanogaster [210] Hepatitis, monkey pox, meningitis, COVID-19, yellow fever, poliomyelitis, small pox, lassa fever Maytenus senegalensis (Lam.) Exell Used to treat opportunistic infections in PLHIV, wound, chest pain, rheumatism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the methanol extract of fifteen plants were screened. At 24 hours, five of the plant extracts namely A. vogelli, C. procera, F. vogelli, S. macrocarpon and T. neriifolia fruit (31.25%) had moderate larvicidal activity (2.0 < LC 50 < 4.2 mg/mL) while the remaining eleven extracts (68.75%) had low activity with LC 50 >4.2 mg/mL [6,26]. After 48 hours of exposure to these test agents, the activities of F. exasperata, P. guajaya, S. alata and T. neriifolia bark improved making the moderately active ones to be 56.3% (Table 3).…”
Section: Discussionmentioning
confidence: 99%